Peranan Pendidikan Islam dalam Meningkatkan Akhlak Siswa di Sekolah Bidayatul Hidayah IV - Afrahul Fadhilah Daulay; Shafira Oktaviola; Ade Husna Prabaswara; Najwa Nabilah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Islamic education is a planned effort to prepare students to understand, believe in, and practice Islamic values. The main aim of this education is to form noble morals in students so that they can benefit themselves and others. This research aims to examine the role of Islamic education in the formation of student morals at the Bidayatul Hidayah IV School. Using a qualitative approach with descriptive methods, data was collected through observation and in-depth interviews with teachers. The research results show that Islamic education at this school involves various religious activities such as memorizing prayers, reading the Koran, and congregational Dhuha prayers. This activity not only increases students' intellectual intelligence but also strengthens their morals and spiritual intelligence. Teachers act as role models in implementing Islamic values, and interactive and fun learning methods help students internalize moral values. This school also emphasizes discipline, responsibility and collaboration between the school, parents and community in supporting the formation of student morals. With a holistic and balanced educational approach, Bidayatul Hidayah IV School has succeeded in forming individuals who have noble character, strong faith, and are ready to face life's challenges wisely. The Islamic education implemented shows a significant positive impact on the development of students' character, creating a young generation with integrity and making positive contributions to society.